Pendampingan Upaya Promotif Dan Preventif Dalam Upaya Penanggulangan Faktor Risiko Kejadian Diare Di Kecamatan Selemadeg Timur Kabupaten Tabanan - I G A M Aryasih; Ni Made Marwati; I Made Bulda Mahayana; D A A Posmaningsih (Poltekkes Kemenkes Denpasar, 2019)
Diarrhea is an environment-based endemic disease that needs serious attention. One factor related to the occurrence of diarrhea is the inadequacy of feces disposal facilities. In an effort to reduce the incidence of diarrhea in the Selemadeg Timur region, Tabanan Regency needs to intervene in the form of community empowerment. The method used is health promotion. The target community is the community in the Banjar Office of Gunung Salak, Gunung Salak Village, East Selemadeg District. Community service is conducted from June to October 2018. The results obtained are a decrease in risk factors for the occurrence of diarrhea below 50% with an average reduction of 22.5% from each assessment item and the construction of a pilot latrine in Gunung Salak Village. The development was carried out with funding sources from the Denpasar Poltekkes and non-government organizations with a ratio of 40%: 60%. The community independently made efforts to improve the quality of environmental sanitation by managing waste and feces in a sanitary manner and handling household waste properly. Puskesmas to carry out health promotion activities, conduct sanitation inspections, and improve the quality of community sanitation and provide assistance to communities that do not yet have qualified latrines.Keywords: Health promotion, healthy latrines, risk of diarrheaDiarrhea is an environment-based endemic disease that needs serious attention. One factor related to the occurrence of diarrhea is the inadequacy of faeces disposal facilities. In an effort to reduce the incidence of diarrhea in the Selemadeg Timur region, Tabanan Regency needs to intervene in the form of community empowerment. The method used is health promotion. The target community is the community in the Banjar Office of Gunung Salak, Gunung Salak Village, East Selemadeg District. Community service is conducted from June to October 2018. The results obtained are a decrease in risk factors for the occurrence of diarrhea below 50% with an average reduction of 22.5% from each assessment item and the construction of a pilot latrine in Gunung Salak Village. The development was carried out with funding sources from the Denpasar Poltekkes and non-government organizations with a ratio of 40%: 60%. The community independently made efforts to improve the quality of environmental sanitation by managing waste and feces in a sanitary manner and handling household waste properly. Puskesmas to carry out health promotion activities, conduct sanitation inspections, and improve the quality of community sanitation and provide assistance to communities that do not yet have qualified latrines.Keywords: Health promotion, healthy latrines, risk of diarrhea